Taxonomic update of the Neotropical genus Cryptocladocera Bezzi, 1923 (Diptera: Tachinidae), with remarks on tachinids with fissicorn antennae - de Santis, Marcelo Domingos; Alvarez-Garcia, Deivys M.; Pereira, Thalles Platiny Lavinscky (Zootaxa, 2020)
Cryptocladocera Bezzi, 1923 is a Neotropical genus of Tachinidae with remarkable multifissicorn antennae, previously composed of four species. A new species from Brazil, Cryptocladocera arnaudi Santis & Alvarez-Garcia sp. nov., is described, illustrated and photographed herein. Cryptocladocera bezzii Arnaud, 1963 and Cryptocladocera mojingensis Arnaud, 1963 are proposed as junior synonyms of Cryptocladocera prodigiosa Bezzi, 1923, synn. nov. With these changes, Cryptocladocera is left with 3 species: C. arnaudi, C. pichilinguensis Arnaud, 1963 and C. prodigiosa. An updated key to the males of Cryptocladocera species is provided. Furthermore, C. prodigiosa is recorded for the first time for French Guiana and Brazil. Finally, the diversity and evolution of fissicorn antennae in tachinids are discussed.